2018
DOI: 10.25121/pf.2018.19.4.274
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ roślin leczniczych na farmakokinetykę i metabolizm leków syntetycznych

Abstract: Herbs have been used in traditional medicine for centuries. They were often used without restrictions, believing that they are effective and safe. They were not known for their side effects or potential interactions with other concomitant medications. Article describes influence of simultaneous usage of herbs and synthetic drugs taken in the same time regarding potential hazards, side effects and interactions. Pharmacological profile of plant substances which are often used in dietary supplements were also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Producenci żywności często umieszczają hasło "zawiera aloes" na opakowaniach, co gwarantuje im większe zainteresowanie konsumentów (jego dodatek można znaleźć m.in. w napojach, jogurtach czy lodach) [23]. Mając na względzie chęć ulepszenia swoich wyrobów, chętnie sięgają oni po ekstrakt z aloesu ze względu na jego bogaty skład.…”
Section: Wstępunclassified
“…Producenci żywności często umieszczają hasło "zawiera aloes" na opakowaniach, co gwarantuje im większe zainteresowanie konsumentów (jego dodatek można znaleźć m.in. w napojach, jogurtach czy lodach) [23]. Mając na względzie chęć ulepszenia swoich wyrobów, chętnie sięgają oni po ekstrakt z aloesu ze względu na jego bogaty skład.…”
Section: Wstępunclassified
“…The terpenoid fraction contained in the plant inhibits cytochrome CYP2C9, while the flavonoid fraction reduces the activity of cytochromes CYP2C9, CYP1A2, CYP2E1 and CYP3A4. In addition, studies have shown the effect of G. biloba and single substances isolated from it on the activity of P-glycoprotein ( Bogacz et al, 2013 ; Rogowska and Ciermaziak, 2018 ). Li et al (2009) showed that ginkgolide A and B induce hepatic P-glycoprotein, as well as a decrease in the metabolism of nicardipine, a calcium channel blocker.…”
Section: Safety In the Use Of G Biloba Extractmentioning
confidence: 99%
“…Dlatego leki ziołowe oraz różnego rodzaju ziołowe suplementy diety, pomocne w terapii niektórych schorzeń psychicznych, zyskują coraz większą popularność, co łatwo można zauważyć, zapoznając się z ofertą handlową aptek i sklepów zielarskich. Jednak substancje roślinne mogą również wchodzić w interakcje z lekami, dlatego przy stosowaniu leków na receptę należy skonsultować spożywanie każdego innego preparatu z lekarzem [14].…”
unclassified